Kids Consumer Behavior in the Internet - Новожилова, М (Journal of Economic Sociology, 2011)
The article is devoted to consumer behavior of kids in the Internet. New consumer patterns have appeared and the old ones have changed because of increasing intervention of the Internet when each internet-user can buy any good or service by a few clicks without visiting traditional off-line shops. The emergence of new behavioral patterns definitely affects the young audience of the Internet. Children start using the cyberspace to consume goods and services. They also learn new norms and behavioral patterns in the process of this consumer socialization. At the same time, there are no widely accepted explanations of the impact of the Internet on formation of consumer patterns of Russian children aged 8 to 12. The aim of this research is to understand how children using Internet form new consumer skills, relations and abilities and to foresee the future development in the area. The paper is based on the online-survey of 1273 kids aged 8 to 12 visiting social web Tvidi.ru